Accelerating the energy transition through innovation (International Renewable Energy Agency, 2017)
Technological breakthroughs are needed to reduce carbon emissions in the energy sector. Even with economically viable and scalable renewable-based solutions available for around two-thirds of the world's energy supply, population growth and rising energy demand could outpace energy decarbonisation without urgent investments in research and development (R&D). This working paper from the International Renewable Energy Agency (IRENA) examines the basic conditions required to nurture innovation and produce new technologies for a low-carbon future. Successful innovation should encompass the complete technology lifecycle. The policy framework for innovation, similarly, must provide balanced support, addressing both technologies themselves and factors beyond technology, including system operations, market design and regulations, and the enabling infrastructure to scale up renewables.